Spójność systemu finansowania jednostek samorządu terytorialnego a ich autonomia finansowa - Turała, Maciej (Coherence of the System of Financing Local Governments and their Financial Autonomy, 2006)
Poland has been witnessing a debate on the autonomy of local governments for many years now. The most important issues that are being raised refer to financial autonomy of local governments as well as to the coherence of the system of financing local governments. This article proposes a method of assessing the level of financial autonomy through an analysis of income-based and expenditure-based financial autonomy. On the other hand it relates to the issue of coherence of the system of financing local governments, which is defined herein as suitability of resources available to local governments to the tasks that they are to perform.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 569-579